Angola : Staff Report for the 2012 Article IV Consultation and Post Program Monitoring. (IMF Staff Country Reports; Country Report, 2012)
The Angolan government's efforts to achieve macroeconomic stability to bring inflation and fiscal deficit considerably down are paying off despite high vulnerability to oil revenue shocks. The expected overall growth of up to 7 percent will be contributed to by increased oil production, multiple public investment programs, tax administration reforms, and inflation control. Concentrating on a medium-term fiscal framework, structural transformation and diversification are expected to reinforce the economy. The Executive Board, which welcomed the Stand-By-Arrangement and Financial Sector Assessment Program (FSAP), suggested removing exchange restrictions.